Phosphoinositide metabolism, lithium and manic depressive illness. Issue 3 (2002) - Yildiz Yildiz, Aysegul Aysegul
Abstract : Physiology underlying manic depressive illness and treating effects of its most commonly used remedy – "lithium" is yet to be elucidated. Recent years of psychopharmacology research witnessed sparkling developments in our understanding of the mechanisms underlying lithium's mood stabilizing effects. Recent data on molecular biology and in vivo magnetic resonance spectroscopy suggest that some of the initial actions of lithium may occur through the inhibition of the enzyme inositol monophosphatase (IMPase) and reduction of myo –inositol, which in turn initiate a cascade of events at different levels of signal transduction process and gene expression in brain; such as the effects on protein kinase C, myristoylated alenine rich C kinase substrate protein, glycogen synthase kinase 3 β, B cell lymphoma–2 protein, and activator protein–I. It is likely that the enzyme IMPase other that being the key point in initiating lithium's therapeutic effects, may also play a critical role in the physiology underlying manic depressive illness.